Fed-batch cultivation of saccharomyces cerevisiae in a hyperbaric bioreactor - Belo, Isabel (2003)
Fed-batch is the dominating mode of operation in high-cell-density cultures of Saccharomyces cerevisae in processes such as the production of baker’s yeast and recombinant proteins, where the high oxygen demand of these cultures makes its supply an important and difficult task. The aim of this work was to study the use of hyperbaric air for oxygen mass transfer improvement on S. cerevisiae fed-batch cultivation. The effects of increased air pressure up to 1.5 MPa on cell behavior were investigated. The effects of oxygen and carbon dioxide were dissociated from the effects of total pressure by the use of pure oxygen and gas mixtures enriched with CO2. Fedbatch experiments were performed in a stirred tank reactor with a 600 mL stainless steel vessel. An exponential feeding profile at dilution rates up to 0.1 h-1 was used in order to ensure a subcritical flux of substrate and, consequently, to prevent ethanol formation due to glucose excess. The ethanol production observed at atmospheric pressure was reduced by the bioreactor pressurization up to 1.0 MPa. The maximum biomass yield, 0.5 g g-1 (cell mass produced per mass of glucose consumed) was attained whenever pressure was increased gradually through time. This demonstrates the adaptive behavior of the cells to the hyperbaric conditions. This work proved that hyperbaric air up to 1.0 MPa (0.2 MPa of oxygen partial pressure) could be applied to S. cerevisiae cultivation under low glucose flux. Above that critical oxygen partial pressure value, i.e., for oxygen pressures of 0.32 and 0.5 MPa, a drastic cell growth inhibition and viability loss were observed. The increase of carbon dioxide partial pressure in the gas mixture up to 48 kPa slightly decreased the overall cell mass yield but had negligible effects on cell viability.